Above‐ and belowground drivers of intraspecific trait variability across subcontinental gradients for five ubiquitous forest plants in North America. (8th May 2022) - Cardou, Françoise; Munson, Alison D.; Boisvert‐Marsh, Laura; Anand, Madhur; Arsenault, André; Bell, F. Wayne; Bergeron, Yves; Boulangeat, Isabelle; Delagrange, Sylvain; Fenton, Nicole J.; Gravel, Dominique; Hamel, Benoît; et al.
Abstract: Intraspecific trait variability (ITV) provides the material for species' adaptation to environmental changes. To advance our understanding of how ITV can contribute to species' adaptation to a wide range of environmental conditions, we studied five widespread understorey forest species exposed to both continental‐scale climate gradients, and local soil and disturbance gradients. We investigated the environmental drivers of between‐site leaf and root trait variation, and tested whether higher between‐site ITV was associated with increased trait sensitivity to environmental variation (i.e. environmental fit). We measured morphological (specific leaf area: SLA, specific root length: SRL) and chemical traits (Leaf and Root N, P, K, Mg, Ca) of five forest understorey vascular plant species at 78 sites across Canada. A total of 261 species‐by‐site combinations spanning 4300 km were sampled, capturing important abiotic and biotic environmental gradients (neighbourhood composition, canopy structure, soil conditions, climate). We used multivariate and univariate linear mixed models to identify drivers of ITV and test the association of between‐site ITV with environmental fit. Between‐site ITV of leaf traits was primarily driven by canopy structure and climate. Comparatively, environmental drivers explained only a small proportion of variability in root traits: these relationships were trait specific and included soil conditions (Root P), canopy structure (Root N) and neighbourhood composition (SRL, Root K). Between‐site ITV was associated with increased environmental fit only for a minority of traits, primarily in response to climate (SLA, Leaf N, SRL). Synthesis . By studying how ITV is structured along environmental gradients among species adapted to a wide range of conditions, we can begin to understand how individual species might respond to environmental change. Our results show that generalisable trait–environment relationships occur primarily aboveground, and only accounted for a small proportion of variability. For our group of species with broad ecological niches, variability in traits was only rarely associated with higher environmental fit, and primarily along climatic gradients. These results point to promising research avenues on the various ways in which trait variation can affect species' performance along different environmental gradients. Abstract : By studying how ITV is structured along environmental gradients among species adapted to a wide range of conditions, we can begin to understand how individual species might respond to environmental change. Our results show that generalisable trait–environment relationships occur primarily aboveground, and only accounted for a small proportion of variability. For our group of species with broad ecological niches, variability in traits was only rarely associated with higher environmental fit, and primarily along climatic gradients. These results point to promising research avenues on the various ways in which trait variation can affect species' performance along different environmental gradients. Résumé: La variabilité intraspécifique des traits (VIT) fournit le matériel nécessaire à l'adaptation des espèces aux changements environnementaux. Pour mieux comprendre comment la VIT peut contribuer à l'adaptation des espèces à un large éventail de conditions environnementales, nous avons étudié cinq espèces forestières de sous‐bois très répandues, exposées à la fois à des gradients climatiques à l'échelle continentale et à des gradients locaux de conditions édaphiques et de perturbation. Nous avons étudié les déterminants environnementaux de la variation intraspécifique des traits foliaires et racinaires. Nous avons ensuite testé si une VIT inter‐site (d'un site à l'autre) plus élevée était associée à une sensibilité accrue des traits à la variation environnementale (c.‐à‐d. un ajustement environnemental). Nous avons mesuré les traits morphologiques (surface foliaire spécifique, SFS; longueur racinaire spécifique, LRS) et chimiques (N, P, K, Mg, Ca des feuilles et des racines) de cinq espèces vasculaires de sous‐bois dans 78 sites au Canada. Un total de 261 combinaisons d'espèces par site couvrant approx. 4300 km a été échantillonné, représentant d'importants gradients abiotiques et biotiques (composition du voisinage, structure de la canopée, conditions du sol, climat). Nous avons utilisé des modèles linéaires mixtes univariés et multivariés pour identifier les déterminants de la VIT inter‐site et tester l'association de la VIT inter‐site avec l'ajustement environnemental. La VIT inter‐site des traits foliaires était principalement déterminée par la structure de la canopée et le climat. En comparaison, les facteurs environnementaux n'expliquaient qu'une faible proportion de la variabilité des traits racinaires : ces relations étaient spécifiques à chaque trait, incluant les conditions du sol (P racinaire), la structure de la canopée (N racinaire) et la composition du voisinage (LRS, K racinaire). La VIT inter‐site n'était associée à un ajustement environnemental accru que pour une minorité de traits, principalement en réponse au climat (SFS, N foliaire, LRS). Synthèse . En étudiant la façon dont la VIT est structurée le long des gradients environnementaux parmi des espèces adaptées à un large éventail de conditions, nous pouvons commencer à comprendre comment ces espèces peuvent répondre aux changements environnementaux. Nos résultats montrent que des associations trait‐environnement généralisables existent principalement au‐dessus du sol et ne représentent qu'une faible proportion de la variabilité. Pour notre groupe d'espèces ubiquistes, la variabilité des traits n'était que rarement associée à un meilleur ajustement environnemental, et principalement le long des gradients climatiques. Ces résultats soulèvent des pistes de recherche prometteuses sur les différentes façons dont la variation des traits peut affecter la performance des espèces le long de différents gradients environnementaux.